MOSQUE ARCHITECTURE AS A SUSTAINABLE BUILDING IN URBAN (Case Study: Al Markas Al Islamic Mosque Makassar) - Imriyanti, Imriyanti (Journal of Islamic Architecture, 2013)
AbstractMosque Architecture is a part of Islamic architecture. Mosque should be fused with elements of nature because its function as a place to pray to God who created the universe. Al Markas Al Islamic Makassar mosque is used as a center of Islamic aspirations of the people and the government to accommodate all the activities of moslems in Makassar. Through this function, the provision of Al Markas Al Islamic mosque began from the desire of Islamic societies in Makassar, which wants the Islamic center to be equipped with facilities and infrastructure as well as architectural, monumental buildings and structures that can be last for hundreds of years (continuous), blend with the environment, and also can be used by the public. Having regard to the function of a mosque especially at the Al Markas Al Islamic Makassar mosque, then the problem that arise is how the Al Markas Al Islamic mosque can be survived/sustainable  in order  to function  as a place  of worship  and  as a center  of Islam.  This research  is a descriptive qualitative research that is trying to generate data in the form of systematic and accurate picture of the object of study. The sustaiprophetlity  of Al Markas AL Islamic mosque can be known through the concept of Islam  in accordance with the view of Islam as well as the sustaiprophetlity of the buildings that seen in the spatial pattern of the mosque, appearance, natural lighting, natural ventilation, and user behavior of the mosque.Keywords: mosque architecture, sustaiprophetlity, view of Islam  AbstrakArsitektur masjid merupakan bagian dari arsitektur Islam. Bangunan masjid sebaiknya dapat menyatu dengan unsur alam karena masjid difungsikan sebagai wadah dalam bersujud/sembahyang  kepada Allah SWT yang menciptakan alam semesta ini. Masjid Al Markas Al Islamic Makassar merupakan kompleks kegiatan Islam yang digunakan sebagai pusat aspirasi masyarakat  dan pemerintahan  yang dapat menampung  seluruh kegiatan  umat Islam di Makassar. Melalui fungsi inilah maka  pengadaan masjid Al Markas Al-Islamic bermula dari keinginan masyarakat Islam di kota Makassar, yang mana menginginkan pusat kegiatan Islam yang dilengkapi dengan sarana dan prasarana juga bangunannya monumental yang secara arsitektur dan struktur bisa bertahan sampai ratusan tahun (berkelanjutan), dan menyatu dengan lingkungannya  serta dapat digunakan  oleh masyarakat  luas. Dengan memperhatikan  fungsi masjid terutama pada masjid Al Markas Al Islamic Makassar maka permasalahan yang muncul adalah bagaimanakah arsitektur  masjid  Al  Markas  Al  Islamic  dapat  bertahan/berkelanjutan   agar  dapat  difungsikan  sebagai  tempat beribadah dan sebagai pusat kegiatan Islam. Penelitian ini merupakan penelitian deskriptif yang bersifar kualitatif yaitu penelitian yang berusaha menghasilkan data berupa gambaran yang sistematis dan akurat dari objek kajian. Keberlanjutan  masjid Al Markas Al Islamic dapat diketahui melalui penyatuan konsep masjid Al Markas Al Islamic sesuai  dengan  pandangan  Islam  serta  keberlanjutan  dilihat  pada  bangunan  yakni  pola  tata  ruang  masjid, penampilan, pencahayaan dan penghawaan alami serta perilaku pemakai masjid.Kata Kunci : Arsitektur masjid, keberlanjutan, pandangan Islam